iTAP, a novel iRhom interactor, controls TNF secretion by policing the stability of iRhom/TACE - Oikonomidi, Ioanna; Burbridge, Emma; Cavadas, Miguel; Sullivan, Graeme; Collis, Blanka; Naegele, Heike; Clancy, Danielle; Brezinova, Jana; Hu, Tianyi; Bileck, Andrea; Gerner, Christopher; Bolado, Alfonso; et al. (eLife, 2018)
The apical inflammatory cytokine TNF regulates numerous important biological processes including inflammation and cell death, and drives inflammatory diseases. TNF secretion requires TACE (also called ADAM17), which cleaves TNF from its transmembrane tether. The trafficking of TACE to the cell surface, and stimulation of its proteolytic activity, depends on membrane proteins, called iRhoms. To delineate how the TNF/TACE/iRhom axis is regulated, we performed an immunoprecipitation/mass spectrometry screen to identify iRhom-binding proteins. This identified a novel protein, that we name iTAP (iRhom Tail-Associated Protein) that binds to iRhoms, enhancing the cell surface stability of iRhoms and TACE, preventing their degradation in lysosomes. Depleting iTAP in primary human macrophages profoundly impaired TNF production and tissues from iTAP KO mice exhibit a pronounced depletion in active TACE levels. Our work identifies iTAP as a physiological regulator of TNF signalling and a novel target for the control of inflammation.
Keywords: cell biology; TACE/ADAM17; buněčné linie; myši; signální transdukce; Gene Expression Regulation; Protein Binding; Sequence Homology, Amino Acid; Primary Cell Culture; sekvenční seřazení; TNF-alfa; Mice, Knockout; chemical biology; Tumour Necrosis Factor (TNF); inflammation; myši knockoutované; lidé; cytoskeletální proteiny; mouse; fibroblasty; Signal Transduction; primární buněčná kultura; sekvence aminokyselin; Humans; protein ADAM17; Intracellular Signaling Peptides and Proteins; proteolýza; biochemistry; vesicular trafficking; iRhom2; ADAM17 Protein; makrofágy; Mice; Animals; Tumor Necrosis Factor-alpha; endozomy; myši inbrední C57BL; sekvenční homologie aminokyselin; zvířata; HEK293 buňky; vazba proteinů; Endosomes; lysosome; RAW 264.7 buňky; HeLa buňky; Carrier Proteins; Fibroblasts; intracelulární signální peptidy a proteiny; Mice, Inbred C57BL; regulace genové exprese; HeLa Cells; Sequence Alignment; human; Macrophages; FRMD8; Proteolysis; Membrane Proteins; membránové proteiny; Cytoskeletal Proteins; Cell Line; transportní proteiny; Amino Acid Sequence; HEK293 Cells; RAW 264.7 Cells